Computational drug discovery of phytochemical alkaloids targeting the NACHT/PYD domain in the NLRP3 inflammasome - Nilay Singh; Promila Sharma; Manoj K. Pal; Ragini Kahera; Himani Badoni; Kumud Pant; Neetu Sharma; Bhawana Bhist (Scientific Reports)
Abstract The NLRP3 inflammasome plays a pivotal role in the innate immune system, orchestrating the activation of caspase-1 and the release of proinflammatory cytokines IL-1β and IL-18 in reaction to microbial infections and cellular damage. Despite its crucial function in defending against pathogens, the dysregulated activation of the NLRP3 inflammasome has been associated with various inflammatory disorders. In the current investigation, promising plant-derived alkaloids compounds have been discovered as targeted inhibitors against multiprotein NLRP3 using an in-silico drug development approach. The repurposing of natural compounds as anti-inflammatory agents remains a relevant approach for identifying promising early interventions to prevent and manage inflammatory diseases. In this molecular docking study targeting Chain A of the NLRP3 inflammasome protein, eight plant-derived alkaloids renowned for their anti-inflammatory properties were chosen. Docking analysis of the selected alkaloids showed the lowest/best binding energies of less than − 10 Kcal/mol against NLRP3 Chain A, based on this docking result, which is regarded as an exceptional binding score. Notably, Oxyacanthine, Magnoflorine, Corynoline, and Berbamine demonstrated the most favourable binding energies, displaying unique interactions within the binding pocket of the NACHT/PYD domain of NLRP3 Chain A among all compounds investigated. These findings highlight the potential of these alkaloids as promising therapeutic candidates specifically targeting this trans-activating NACHT/PYD domain of NLRP3 Chain A in the context of anti-inflammatory interventions. Protein-protein interactions (PPIs) play an important role in elucidating protein function and drug interactions. To identify bioactive compounds with anti-inflammatory potential, a functional protein network was constructed from publicly available PPI data. As a result, the findings of this in-silico study may cause researchers to emphasize more on alkaloids when considering natural plant products for the treatment of various illnesses that target the inflammatory intermediates. This computational approach predicted ligands that may modulate inflammatory proteins and support host immunity. However, further in vitro and in vivo studies are still needed to validate these in-silico findings before clinical use. In summary, analysing PPI networks can aid discovery of therapeutic candidates, but experimental validation remains essential.